2021
DOI: 10.3390/allergies1010006
|View full text |Cite
|
Sign up to set email alerts
|

IgE-Binding Epitopes of Pis v 1, Pis v 2 and Pis v 3, the Pistachio (Pistacia vera) Seed Allergens

Abstract: Sequential IgE-binding epitopes were identified on the molecular surface of the Pis v 1 (2S albumin), Pis v 2 (11S globulin/legumin) and Pis v 3 (7S globulin/vicilin)—major allergens from pistachio (Pistacia vera) seeds—using the Spot technique. They essentially consist of hydrophilic and electropositively charged residues well exposed on the surface of the allergens. Most of the epitopic regions identified on Pis v 1 and Pis v 3 do not coincide with the putative N-glycosylation sites and thus are not consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…18 Curiously, a PD search comparing the tomato and buckwheat VBPs shown in Figure S2 against this same 13cp reveals comparable scores to the peanut/walnut VBPs, suggesting that this mode of cross-reactivity is applicable to other food allergen sources beyond the peanut and walnut sequences described in this work. Finally, it should also be noted that IgE-reactive VBPs have also been identified in almonds (Pru du 8), 46 cashew (Ana o 1), 47 pistachio (Pis v 3), 48,49 sesame (Ses i 3), 49 and macadamia nut (Mac i 1). 50 While the structure of these IgE-reactive VBPs has yet to be solved, their sequences share similar PD scores when compared against the 13cp as their peanut and walnut homologues.…”
Section: ■ Discussionmentioning
confidence: 99%
“…18 Curiously, a PD search comparing the tomato and buckwheat VBPs shown in Figure S2 against this same 13cp reveals comparable scores to the peanut/walnut VBPs, suggesting that this mode of cross-reactivity is applicable to other food allergen sources beyond the peanut and walnut sequences described in this work. Finally, it should also be noted that IgE-reactive VBPs have also been identified in almonds (Pru du 8), 46 cashew (Ana o 1), 47 pistachio (Pis v 3), 48,49 sesame (Ses i 3), 49 and macadamia nut (Mac i 1). 50 While the structure of these IgE-reactive VBPs has yet to be solved, their sequences share similar PD scores when compared against the 13cp as their peanut and walnut homologues.…”
Section: ■ Discussionmentioning
confidence: 99%
“…50 Nonetheless, it is becoming increasingly evident that plant VBPs represent an important immunogenic species that can mediate both allergic sensitization and cross-reactive IgE binding across a range of common food sources including peanuts and tree-nuts. Recent works identifying IgE-reactive sequences on VBPs from macadamia nuts, sesame, and almonds 7,10,15,51 further emphasize their immunological potential. The structural and immunological data presented in this work suggests that VBPs from cashews and pistachios could mediate both cashew/pistachio allergy and cross-reactivity with peanut and other tree-nut counterparts via a conserved hairpin motif, with implications for both molecular diagnostic and allergen avoidance strategies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The vicilin protein is expressed with an N-terminal leader sequence (LS), which contains a variable number of vicilin-buried peptides (VBPs) that are cleaved from the parent vicilin during the maturation process . IgE-reactive VBPs have been identified in peanuts and tree-nuts such as walnuts, cashews, and pistachios. The allergen vicilin with the most VBPs is the recently described hazelnut allergen Cor a 16 with a dozen . Previous studies on the peanut LS that contains one VBP domain (AH1.1) revealed that IgE binding levels are uncorrelated to its larger parent vicilin, suggesting that these VBP sequences represent a new allergen family whose immunological properties are independent of their parent vicilins …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the epitopic regions of Pis v 1 and Pis v 3 showed a high degree of similarity with the Ana o 1, Ana o 2 and Ana o 3 epitopes. This is considered to be the molecular basis for the IgE-binding cross-reactivity observed between pistachios and cashews [29]. In almonds, six allergenic proteins have been characterized: Pru du 3 (LTP), Pru du 4 (profilin), Pru du 5 (60S ribosomal protein), Pru du 6 (11S legumin), Pru du 8 (antimicrobial seed storage protein) and Pru du 10 (mandelonitrile lyase 2) [30].…”
Section: Most Prevalent Allergenic Nuts and Their Predominant Allergensmentioning
confidence: 99%